(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-640-2021-4-194-206 The article is devoted to the consideration of the little-studied period in the history of one of the leading newspapers of the Caucasian region – the newspaper «Kavkaz» – from 1900 to 1910. This is a period of frequent change of editors, whose creative biographies require careful research and reconstruction based on archival data, memoirs, reference and newspaper sources. The study of the existing gap is of undoubted interest for the restoration of the general picture of the development of the regional media landscape in the process of cardinal political, economic and socio-cultural shifts, which are reflected in the publishing policy of the analyzed periodical. The first decade of the XX century was marked by a number of structural transformations in the editorial practices of most of newspapers and magazines of the Russian Empire both in capitals and in individual territories, which, in its turn, was associated with the construction of a new system of native parliamentary system of government with all its costs, the emergence of a radicalized party press, changing the existing censorship format. The newspaper «Kavkaz», published in the capital of a huge region, became a kind of «mirror» of all these transformations, tracking the course of events in its constituent regions and provinces. In a paradoxical way, it combined in its content the position of the regional administration and the political preferences of individual editors, entered into discussions on a number of socially significant issues, actively polemicized not only with competing Tiflis press, including those published in Georgian and Armenian languages, but also with the metropolitan newspapers, including the influential newspaper «Novoye Vremya», edited by A.S. Suvorin in St. Petersburg. The main part of the political activity of the newspaper «Kavkaz» was quite expected in 1906-1907, which coincided with the editorial searches of P.A. Opochinin. In the course of the study, a number of bio-bibliographic facts (years of life, pseudonyms, main publications) were restored by editors M.M. Tebenkov, K.N. Begichev, P.A. Opochinin. Key words: newspaper «Kavkaz», editorial body, regional media landscape, publishing policy